Revisiting salicylidene-based anion receptors. Issue 58 (17th November 2021) - Dey, Sandeep Kumar; Kumari, Sonam; Mandrekar, Sonal; Mhaldar, Shashank N.; Harmalkar, Sarvesh S.; Janiak, Christoph
Abstract : Salicylidene Schiff bases undergo imine bond hydrolysis in the presence of halides and oxo-anions in aprotic media, raising fundamental questions on the applicability of salicylidene-based receptors as anion sensors. Abstract : Several salicylidene-based colorimetric and fluorimetric anion sensors are known in the literature. However, our 1 H-NMR experimental results (in DMSO-d6 ) showed hydrolysis of imine (–NCH–) bonds in salicylidene-based receptors (SL, CL1 and CL2 ) in the presence of quaternary ammonium salts ( n -Bu4 N + ) of halides (Cl − and Br − ) and oxo-anions (H2 PO4 −, HSO4 − and CH3 COO − ). The mono-salicylidene compound CL1 showed the most extensive –NCH– bond hydrolysis in the presence of anions. In contrast, the di-salicylidene compound CL2 and the tris-salicylidene compound SL showed comparatively slow hydrolysis of –NCH– bonds in the presence of anions. Anion-induced imine bond cleavage in salicylidene compounds could easily be detected in 1 H-NMR due to the appearance of the salicylaldehyde –CHO peak at 10.3 ppm which eventually became more intense over time, and the –NCH– peak at 8.9–9.0 ppm became considerably weaker. Furthermore, the formation of the salicylidene O–H⋯X − (X − = Cl − /Br − ) hydrogen-bonded complex, peak broadening due to proton-exchange processes and keto–enol tautomerism have also been clearly observed in the 1 H-NMR experiments. Control 1 H-NMR experiments revealed that the presence of moisture in the organic solvents could result in gradual hydrolysis of the salicylidene compounds, and the rate of hydrolysis has further been enhanced significantly in the presence of an anion. Based on 1 H-NMR results, we have proposed a general mechanism for the anion-induced hydrolysis of imine bonds in salicylidene-based receptors.